Orbital bone fractures: 10 years' experience at the Rome trauma centre: retrospective analysis of 543 patients. Issue 10 (December 2022) - Priore, Paolo; Di Giorgio, Danilo; Marchese, Gloria; Della Monaca, Marco; Terenzi, Valentina; Battisti, Andrea; Fadda, Mariateresa; Valentini, Valentino
Abstract: Orbital fractures are among the most frequent facial traumas. This study retrospectively analysed patients treated in Umberto I Hospital Trauma-Centre, Sapienza University of Rome from 1 January 2010 to 31 December 2020. The inclusion criteria were as follows: diagnosis of pure/impure orbital bone fracture, complete clinical and radiological records, and a minimum 12-month follow up. Gender, age, aetiology, fracture type, treatment, and associated complications were analysed using IBM SPSS Statistics, and p values of <0.05 were considered significant. In total, 1393 patients presented with orbital trauma, 543 of whom met the inclusion criteria and underwent surgery (394 males (72.6%) and 149 females (27.4%); mean (range) age 39.2 (7–90) years). Assault (n = 165, 30.4%) was the most common cause of trauma, followed by road traffic accidents and sports-related incidents. Diplopia was the major symptom at diagnosis (n = 183, 33.6%). Open reduction and internal fixation via a sub-eyelid approach was the preferred treatment, achieving a significant reduction in the functional changes induced by fracture (p < 0.05). Our data will aid future studies of maxillofacial traumatology and suggest that education and prevention measures could reduce the incidence of this type of trauma.